Challenges facing anti-corruption mechanisms in dominant party systems: a case study of KwaZulu-Natal in South Africa, 2004-2019 - Mchunu, Ngqapheli (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2023.